Association between height and sleep duration in Korean adults. Issue 2 (25th February 2021) - Seo, Min‐Seok; Hwang, In Cheol
Abstract: The relationship between height and sleep duration is poorly understood in adults. We analysed the data from 32 698 adults collected by the 2007–2016 Korean National Health and Nutrition Examination Survey. A total of 44.4% and 9.1% participants reported short (≤6 h) and long (≥9 h) sleep duration, respectively. A shorter height was significantly associated with increased likelihood of both short and long sleep. A sex‐stratified analysis revealed that the relationship between height and sleep duration was only significant in males. In conclusion, height was independently related to sleep duration in Korean men.